Analisis Neraca Air Lahan untuk Perencanaan Tanaman Padi Gogo dan Jagung pada Sub Das Wolasi - Sani, Nur Fitria; Darwis, Darwis; Alam, Syamsu; Rustam, Rustam; Leomo, Siti; Erawan, Dedi (Jurnal Agroteknologi (Agronu), 2024)
Infomation climate data of a place plays an important role in the development of agriculture in the region. This can be used to find out about the relationship between plants and climate, estimates of planting time, harvest time, drought (water deficit), flooding (water surplus) can be made, and determining the types of plants used. In accordance. This study aims to determine the level of groundwater availability based on land water balance analysis in the Wolasi sub-watershed and to find out how to plan planting patterns of upland rice and corn according to groundwater availability in the Wolasi sub-watershed. This study uses monthly rainfall data for 10 years (2012-2021) and other climate data (air temperature) for 10 years (2012-20121). Calculation of land water balance using the Throntwaite-Mather method. The result of land water balance calculation under conditions of monthly average rainfall distribution of water availability in the Wolasi sub-watershed are classified as very adequate where a surplus occurs from January to July and December. While the water deficit occurs from August to October. At a 75% chance of rainfall, the distribution of water availability is classified as very adequate,where a surplus occurs from January to July and November to December and a water deficit occurs from July to October. In the Wolasi sub-watershed, the montly average rainfall for upland rice can be planted in January and the final harvest in April, while for corn, the initial planting can be done in May and the final harvest in July, upland rice and corn can be planted twice in a row. a year and can also be planted in intercropping. With a 75% chance of rainfall in the Wolasi sub-watershed, the initial planting of upland rice can be done in January and the final harvest in April, while corn plants can be intercropped, planting upland rice and corn can be done once a year.